Thermoplastic Waste Composite Brick As An Environmentally Friendly Material - Safarizki, Hendramawat Aski; Ristanto, Iwan; Sangadji, Senot; Karno, Muhammad Febrialdi; Dewi, Amelia Putri (ASTONJADRO, 2026)
The background of this research is that plastic waste is abundantly available around us and has not been optimally utilized. Pedestrian which is also the right of pedestrians with disabilities has not been well organized in Indonesia. The use of plastic waste materials is an alternative to solving environmental problems. The utilization of plastic as a substitute for cement will also reduce the carbon effect of cement as a building material. With its light weight when compared to disabled terrazzo tiles on the market, it is hoped that it can facilitate the application of smart pedestrian blocks as pedestrian paths and disabilities. The purpose of this research is the utilization of plastic waste as used as composite thermoplastic waste brick as well as an alternative eco friendly material. The experimental method used normal paving, 45% plastic waste, 55% plastic waste, and 65% plastic waste. The test results show that the average compressive strength for paving with 45% plastic waste has a compressive strength of 9.16 MPa higher than normal paving which is only 8.56 MPa. This shows that the use of 45% plastic waste as an effective substitute for cement in paving is also an environmentally friendly solution. In addition to reducing plastic waste, it also reduces the need for cement.